The Application Of Learning Principles For The Teaching Of English At SMAN 2 Ngawi (A Naturalistic Study) - Ludfiani, Nungki Kus, Prof. Dr. Endang Fauziati, M. Hum, Agus Wijayanto, Ph.D (2014)
The thesis describes the learning principles applied to teaching English at SMAN 2 Ngawi. By doing the research, the researcher could investigate the learning principles reflected in English teaching process at SMAN 2 Ngawi, the classroom activities which are based on the learning principles used by the teachers as well as the teacher's purpose in using such classroom activities. Subjects of the research are three English teachers teaching at SMAN 2 Ngawi. The data collection was conducted through observation, interview and documentation. The data collected were analyzed qualitative. The findings of the research show that the three teachers applied the four learning principles in their teaching process through various kinds of classroom activities with certain purposes. The learning principles are the perspective in teaching English so the teachers can use the findings to assist them in teaching the students .Teachers can enrich themselves with various teaching techniques or classroom activities to make the lesson more attractive and meet the students' need.